Black on Red: Late-Nineteenth and Early-Twentieth-Century New World Black Interpretative Uses of Native American Political Experience. (September 2019) - Gordon, Jane Anna; Lindsay, Keisha
Abstract: In an effort to address the dearth of literature regarding how African American political theorists have historically interpreted the meaning of Native political experience to make sense of their own, we chart what four influential New World Black writers, from the nineteenth and early-twentieth centuries, say about Native Americans. While there is some diversity among the particular interpretive foci of these historical works, each generally invokes Native Americans as having a shared experience of oppression with Blacks that warrants resistance; being crushed by circumstances in which African-descended people have survived and thrived; exemplifying oppression that has no redemptive power; providing evidence of the ongoing possibility of Black extinction; and as racially inferior to Blacks and thus in need of Black ladies' supposedly civilizing qualities. This paper uses these historical Africana perspectives on Indigenous and Black relations to explore the political implications of forging individual and shared identities at the intersection of race and gender.